Effect of the Functional Impression on the Alveolar Resorption for the Partial Removable Dentures Patients of Class I of Kennedy (Journal of Hama University, 2019)
Alveolar bone resorption, under free end removable partial dentures bases, has been considered one of most common problems for both of the dentist and  the patient, though the multiple studies and techniques have been achieved to reduce this problem .this research aimed to study the effect of functional impression on the alveolar bone resorption for the Partial Removable Dentures Patients of Class I of Kennedy under cast metal removable partial dentures with flexible acrylic resin bases, depending on two different types of definitive impression .(15) mandibular removable partial denturs of calss I kennedy have been made for (15) patients using  McLean physiologic impression and Selective pressure single impression, then a digital radiographic panoramic image was made for each patient while was wearing the denture, after artificial tooth had been restored by dental Amalgam to be a reference point for measurement. Aafter 6 months the panoramic image has been taken again and the measurement will be done by the Adobe photoshop program.Within the limits of the study showed; The occurrence of alveolar bone resorption with time in disdimilar rate between patients, whatever the type of functional impressiom was used, but with no statistically significant differences, and showed the replication of resorption in the most distal area from the distal abutment in selective pressure single impression group comparing to Mclean physiologic impression group with statistically significant differences.There is no effect of type of functional impression in alveolar bone resorption under cast metal removable partial dentures with flexible acrylic resin bases, with preferable to use the Mclean physiologic impression for this type of dentures.